1993
DOI: 10.1111/j.1752-1688.1993.tb03242.x
|View full text |Cite
|
Sign up to set email alerts
|

VALIDATION OF AGNPS FOR SMALL WATERSHEDS USING AN INTEGRATED AGNPS/GIS SYSTEM1

Abstract: The AGNPS (AGricultural NonPoint Source) model was evaluated for predicting runoff and sediment delivery from small watersheds of mild topography. Fifty sediment yield events were monitored from two watersheds and five nested subwater‐sheds in East Central Illinois throughout the growing season of four years. Half of these events were used to calibrate parameters in the AGNPS model. Average calibrated parameters were used as input for the remaining events to obtain runoff and sediment yield data. These data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 3 publications
3
24
0
Order By: Relevance
“…This was a satisfactory result, attributed to the maximum possible calibration (Table 3). The result confirmed the results obtained by Mitchel et al (1993), Perrone andMadrammooto (1997), andBhuyan et al (2003) in Illinois, Quebec, and Kansas watersheds, respectively, that AGNPS simulates runoff with reasonable accuracy. The model prediction for runoff was much better than obtained by Nigussie and Fekadu (2003), Hassen et al (2004), andLen et al (2004) in the Augucho catchment, Kori watershed, and a southern Ontario watershed, respectively.…”
Section: Runoff In the Calibration Of The Agnps Modelsupporting
confidence: 78%
See 1 more Smart Citation
“…This was a satisfactory result, attributed to the maximum possible calibration (Table 3). The result confirmed the results obtained by Mitchel et al (1993), Perrone andMadrammooto (1997), andBhuyan et al (2003) in Illinois, Quebec, and Kansas watersheds, respectively, that AGNPS simulates runoff with reasonable accuracy. The model prediction for runoff was much better than obtained by Nigussie and Fekadu (2003), Hassen et al (2004), andLen et al (2004) in the Augucho catchment, Kori watershed, and a southern Ontario watershed, respectively.…”
Section: Runoff In the Calibration Of The Agnps Modelsupporting
confidence: 78%
“…The high deviation of the model output for sediment yield was also experienced at Salzbode (Central Germany) with a 51% overestimation (Rode and Frede, 1997). A study conducted in East Central Illinois (USA) on six field-sized watersheds (1.6-30.4 hm 2 ) showed that the yield of simulated annual sediment varied from 25% to 57% of the observed value (Mitchel et al, 1993). The deviations observed in this study can be explained by the scale of the study and the inconsistencies and random errors in the measurements of the observed data.…”
Section: Sediment In the Calibration Of The Agnps Modelmentioning
confidence: 99%
“…This model behavior can be attributed to the Curve Number method for estimation of runoff volume and the direct effect on the modeled peak runoff rate. This is consistent with other calibration attempts (Mitchell et al, 1993). Some authors propose the exclusion of small events when calibrating the AgNPS model (Grunwald & Norton, 2000), because of their minor contribution to runoff and consequently sediment and nutrient transport.…”
Section: Calibrationsupporting
confidence: 75%
“…One worldwide used model for such purposes is the AgNPS or Agricultural Non Point Source pollution model (Young et al, 1989). Past applications included the assessment of soil erosion (Prato & Shi, 1990;Engel et al, 1993;Mitchell et al, 1993;Rainis et al, 2002;Walling et al, 2003), prediction of surface runoff Mitchell et al, 1993;Grunwald & Norton, 2000), assessment of allowable nutrient loads (Pekarova et al, 1999;Rode & Lindenschmidt, 2001), prediction of effects of different land use management practices (Prato & Shi, 1990;Mostaghimi et al, 1997) and simulation of the effect of expanded swine production on P transport and water quality (Sauer et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Poiani and Bedford (1995) recently presented a cursory review of GE-based NPS pollution models emphasizing surface applications. Numerous hydrologic-water quality models of runoff and soil erosion have been used with a GIS to determine surface sources of NPS pollutants from watersheds (Pelletier, 1985;Potter et al, 1986;Oslin et al, 1988;Sivertun et al, 1988;DeRoo et al, 1989DeRoo et al, , 1992Rudra et al, 1991;Bhaskar et al, 1992;Drayton et al, 1992;Joao & Walsh, 1992;Tim et al, 1992;Walker et al, 1992;Wolfe, 1992;He et al, 1993;Heidtke & Auer, 1993;Levine et al, 1993;Mitchell et al, 1993;Warwick & Haness, 1994) agricultural areas (Hopkins & Clausen, 1985;Gilliland & Baxter-Potter, 1987;Hession & Shanholtz, 1988Panuska & Moore, 1991;Hamlett et al, 1992;Lee & White, 1992;Geleta et al, 1994;Tim & Jolly, 1994) and urban areas (Smith & Brilly, 1992;Smith, 1993;Ventura & Kim, 1993). In addition, several groundwater models have been coupled to a GIS to simulate water flow and/or NPS pol-lutants in aquifers (Kernodle & Philip, 1989;Baker & Panciera, 1990;Hinaman, 1993;Roaza et al, 1993;El-Kadi et al, 1994;Darling & Hubbard, 1994).…”
Section: Gis-based Models For Nps Pollution Estimationmentioning
confidence: 99%